The Plasma Membrane-Associated GTPase Rin Interacts with the Dopamine Transporter and Is Required for Protein Kinase C-Regulated Dopamine Transporter Trafficking - Navaroli, Deanna M. (Society for Neuroscience, 2011)
Dopaminergic signaling and plasticity are essential to numerous CNS functions and pathologies, including movement, cognition, and addiction. The amphetamine- and cocaine-sensitive dopamine (DA) transporter (DAT) tightly controls extracellular DA concentrations and half-life. DAT function and surface expression are not static but are dynamically modulated by membrane trafficking. We recently demonstrated that the DAT C terminus encodes a PKC-sensitive internalization signal that also suppresses basal DAT endocytosis. However, the cellular machinery governing regulated DAT trafficking is not well defined. In work presented here, we identified the Ras-like GTPase, Rin (for Ras-like in neurons) (Rit2), as a protein that interacts with the DAT C-terminal endocytic signal. Yeast two-hybrid, GST pull down and FRET studies establish that DAT and Rin directly interact, and colocalization studies reveal that DAT/Rin associations occur primarily in lipid raft microdomains. Coimmunoprecipitations demonstrate that PKC activation regulates Rin association with DAT. Perturbation of Rin function with GTPase mutants and shRNA-mediated Rin knockdown reveals that Rin is critical for PKC-mediated DAT internalization and functional downregulation. These results establish that Rin is a DAT-interacting protein that is required for PKC-regulated DAT trafficking. Moreover, this work suggests that Rin participates in regulated endocytosis.